5 - Analysis of Frames Used by Namibian Newspapers in their Reportage of the San Community - Moses Magadza,; Eno Akpabio, (African Sociological Review, 2020)
Thisstudy involves an analysis of the representation of San people of Namibia in news stories published in The Namibian, New Era, Inf ormanté, The Southern Times, The Villager, The Windhoek Observer and Namibian Sun newspapers over a two-year period - January 2012 to December 2013. A purposive sampling technique was used to select the stories. Content analysis and critical discourse analysis (CDA) were used to analyse data and point out binaries and dichotomies inherent in selected articles. Thestudy found that balanced reportage of issues that affect San people is conspicuously absent. Much of the reportage is event-driven, lacking analysis and balance. Thestudy recommends new media discourses that shift from stereotyping to a discourse that restores and upholds the identity of San people.